Cross-national comparability of burden of disease estimates: the European Disability Weights Project - Essink-Bot Marie-Louise; Pereira Joaquin; Packer Claire; Schwarzinger Michael; Burström Kristina (Bulletin of the World Health Organization, 2002)
OBJECTIVE: To investigate the sources of cross-national variation in disability-adjusted life-years (DALYs) in the European Disability Weights Project. METHODS: Disability weights for 15 disease stages were derived empirically in five countries by means of a standardized procedure and the cross-national differences in visual analogue scale (VAS) scores were analysed. For each country the burden of dementia in women, used as an illustrative example, was estimated in DALYs. An analysis was performed of the relative effects of cross-national variations in demography, epidemiology and disability weights on DALY estimates. FINDINGS: Cross-national comparison of VAS scores showed almost identical ranking orders. After standardization for population size and age structure of the populations, the DALY rates per 100000 women ranged from 1050 in France to 1404 in the Netherlands. Because of uncertainties in the epidemiological data, the extent to which these differences reflected true variation between countries was difficult to estimate. The use of European rather than country-specific disability weights did not lead to a significant change in the burden of disease estimates for dementia. CONCLUSIONS: Sound epidemiological data are the first requirement for burden of disease estimation and relevant between-countries comparisons. DALY estimates for dementia were relatively insensitive to differences in disability weights between European countries.